A corpus-based study of depressive language in online teen health communications - Yu-Hua, Chen; Chen, Jin (University of Nottingham, 2017)
This paper presents a multidisciplinary study by using a corpus linguistic approach to investigate the topic of teen depression in an online discussion forum. The lexico- grammatical and semantic patterns of keywords in 129 online posts are explored, and five keywords (i.e. ‘have’, ‘feel’, ‘know’, ‘want’ and ‘really’) are chosen for investigation. The results suggest that those posts are characterised by recurring expressions associated with intense emotions, which indicate this group’s vulnerable mental state in relation to social contexts (e.g. family, school or relationship), and the semantic prosody of the text excerpts examined is predominantly negative (e.g. ‘I feel so alone and angry’). The findings shed light on the use of language expressions in a unique discourse of online health communications. (120 words)